Saksi sa kasaysayan - Barreiro, Roberto; Flores, Marissa; Sanchez, Leogarda (GMA Network, 2001)
The story of the election and impeachment of President Joseph Ejercito Estrada, told in video news documentary. It shows the highlights of events, from the Senate Blue Ribbon Committee hearings, to the impeachment trial, and the days of People Power II. Saksi sa Kasaysayan is a presentation of the men and women of the GMA News and Public Affairs Division.